Autoethnographic Reflections of an International Graduate Teaching Assistant’s Co-Teaching Experiences - Howlett, Kristina; Nguyen, Huong (Journal of International Students, 2020)
This authoethnographic study explores the co-teaching experiences of an international graduate teaching assistant (IGTA) assigned to co-teach an undergraduate course at a U.S. publicly funded university. As a sociocultural theoretical framework, Dewey (1938), Vygotsky (1978), and Schön’s (1983) works regarding experiential learning, interaction, and reflective practice were used to analyze narratives and highlight the IGTA’s co-teaching experiences to provide evidence of reflective and collaborative practices. Five themes emerged from the study: a need for professional development, interdependence, mentoring, improving interpersonal skills, and shifting perspectives. The findings uncovered how the co-teaching experience cultivated and sustained an IGTA’s personal awareness of self and others through guided reflection on instructional practices to improve teaching and learning.